Streamlining Success: A Study of Best Pre- and Post-Matriculation Practices in Community Colleges - Lance Hawvermale; Richard A. Voorhees (Educational Considerations, 2025)
This study explored student success practices of select community colleges as implemented during students’ pre- and post-matriculation periods and whether those colleges have united them into a cohesive design. The pre- and post-matriculation timeframe has been identified as the most critical segment of the student’s academic career (Acevedo-Gil & Zerquera, 2016; McFadden, 2016). Qualitative data were gathered from key informants at a reputational sample of three community colleges. The research indicated that successful pre- and post-matriculation processes shared several elements in common, including a culture that empowered its employees, a streamlined student experience built on data, and a president who fostered an environment of innovation. Because the pre- and post-matriculation experiences at these colleges are dependent on each other as parts of a single process with a shared goal, they may be considered a system, and their performance in these phases can and should be assessed as a combined entity. By focusing intentionally on streamlining operations, cross-training employees, and consolidating offices into a single space, these colleges built systems designed to dismantle traditional barriers and to guide students into the second semester.
Keywords: Community Colleges; Culture; Matriculation; Leadership